Empirical validation of the time accuracy of the novel process language Human Work Design (MTM-HWD®). Issue 1 (1st January 2019) - Faber, Marco; Przybysz, Philipp; Latos, Benedikt A.; Mertens, Alexander; Brandl, Christopher; Finsterbusch, Thomas; Härtel, Jörg; Kuhlang, Peter; Nitsch, Verena
ABSTRACT: This paper presents the empirical validation of the time accuracy of the process building block system MTM-HWD® (Human Work Design). The analysis is based on process data collected from 62 different workplaces in German manufacturing companies. The accuracy of the process system is analyzed by studying the frequency of employed process building blocks in the data collection procedure. Subsequently, the differences between the MTM-HWD® and MTM-1 cycle times are evaluated. The findings show that there is no significant difference from samples of prior MTM-1 studies with respect to the frequency of employed MTM-1 process building blocks. It is shown that there is a systematic difference and a linear relationship between the MTM-HWD® and MTM-1 time data. However, it is demonstrated that the relatively larger MTM-HWD® times do not differ more than 5 % from the MTM-1 times when considering the 95 % confidence interval of the mean. These results meet the development aims in terms of the defined accuracy of the method of ± 5 % in comparison to MTM-1.